MAPPING THE FIELD, A BIBLIOMETRIC ANALYSIS OF ENVIRONMENT IN ISLAM - Fitria, Laili (Borneo International Journal of Islamic Studies, 2020)
The environmental crisis is happening today requires the attention of the global community. One approach that can be done is to apply the teachings of Islam as a whole. Belief in religion can influence people to maintain the environment. This study was conducted to determine how the environment in Islam. Scientific publications in accordance with Islamic friends in the neighborhood of indexed Dimensions analyzed by a systematic literature review (SLR). The parameters analyzed were the number of publications per year, the origin and the origin of the author's state institutions. Furthermore, the results were analyzed with the VOS Viewer software. A total of 30 relevant scientific articles selected and analyzed. Publications related to the environment in Islam increased since 2006 with some of the topics of discussion. A popular topic of research is on the management of natural resources and environment, water conservation, and climate change.